Impact of hemoglobin concentration on plasma B-type natriuretic peptid level and left ventricle echocardiographics characteristics in chronic kidney disease patients - Ćatović-Rašić, Senija (Array, 2009)
Summary: Anemia is common in patients with chronic kidney disease (CKD) and contributes to cardiovascular alterations. Recent findings suggest that B-type natriuretic peptide (BNP) is a sensitive biomarker for left ventricular dysfunction, but relationship between hemoglobin and BNP in CKD patients is unclear. Hemoglobin, plasma BNP and serum creatinine levels were measured in 49 patients with CKD (without heart failure), divided in two groups according to the hemoglobin status (cut-off point 110 g/L). All patients underwent echocardiography in order to assess left ventricular (LV) morphology and function. The results showed that in the group of patients with hemoglobin levels under 110 g/L BNP levels were significantly elevated (p<0.001), as well as left ventricular mass index (p<0.001). Systolic and diastolic LV function were significantly better in patients with hemoglobin levels above 110 g/L (p<0.001). Hemoglobin levels were inversely related to BNP values (r=–0.451, p<0.001). Significantly negative correlation between BNP level and creatinine clearance (p=0.009), and significantly positive correlation between BNP level and left ventricular mass index (LVMI) were established. A similar but positive relationship was observed between hemoglobin levels and creatinine clearance (p<0.01). We established statistically significant negative correlation between hemoglobin levels and LVMI (r=–0.564, p<0.001). In conclusion, BNP and hemoglobin levels depend on the renal function. Anemia may contribute to elevated BNP levels in CKD patients, and may represent an important confounder of the relationship between BNP and cardiac alteration in these patients